(untitled) (Baghdad Science Journal, 2011)
One of most the important compounds which have active hydrogen (substrate) is the thiols which used in a wide field in preparation of Mannich bases . A large number of Mannich bases have been prepared as a biologically active compound (pharmaceutical, pesticides, bactericidal, fungicidal and tuberculostatic) and in order to correlate their structure and reactivity with their pharmacological activity such as . It has been reported that the reaction is easily proceeded by using primary and secondary amine beside formaldehyde. But when we tried the reaction of thiols as substrate and formaldehyde and succinimide instead of amine, the reaction did not proceed to give Mannich base but product were methylenene – bis – sulfide . Mannich base can go farther reaction such as (addition, substitution, cleavge, polymerization, hydrogenation) to produce numerous numberbof compound so we tried to hydrogenation tetrazole derivative which gave different product which depened on type of hydrogen on reagent. Reduction of 2 – ethyl benzoyle – phenyl tetrazole which performed with hydrogen gas in methanol solution in presence palladium on carbon as catalyst, the tow products were separated by column chromatography. Reduction of 2 – methyl – 2 (2 – cycloheptane) – 5- phenyl tetrazole. The methanolic solution the ketone was refluxed with equimolar amount of potassium borohydride and the product is isolated and purified to give. and identified by C.H.N analysis and NMR spectra.